Incidência de acidente cerebro-vascular embólico na cardiopatia chagásica crônica Chronic Chagas' cardiopathy and cerebrovascular insults - A. Spina-França; N. Yasuda (Arquivos de Neuro-Psiquiatria)
A incidência de acidente vascular cerebral embólico na cardiopatia chagásica crônica foi avaliada a partir de duas séries consecutivas de casos: a primeira compreendendo 63 pacientes com cardiopatia chagásica crônica e, a segunda, 84 pacientes com acidentes cerebrovasculares, 59 dos quais de tipo não hemorrágico. Em relação aos casos de cardiopatia chagásica crônica a incidência de acidente vascular cerebral embólico mostrou-se da ordem de 3,17%; em relação aos acidentes cerebrovasculares, da ordem de 4,76% e quando considerados apenas aqueles de tipo não hemorrágico, da ordem de 6,78%. Mural thrombi in the cavities of the heart are commonly found in chronic Chagas' cardiopathy and embolic phenomena may result from them. Acute cerebrovascular insults resulting from embolic occlusion of cerebral arteries are described in Chagas' disease since 1953. The purpose of this investigation was to evaluate the incidence of this type of cerebrovascular embolic insult. Two groups of patients successively admitted to a general hospital were studied: the first of 63 cases of chronic Chagas' cardiopathy; the second of 84 cases of acute cerebrovascular disease. The brain insult was non-hemorrghagic type in 59 cases of the second group. The evaluation pertinent to the first series showed that embolic cerebrovascular insult occurred in 3.17% of the cases. Concerning the second series the incidence of embolic cerebrovascular insult secondary to chronic Chagas' cardiopathy was 4.76% when all cerebrovascular insults were considered, and 6.78% when only non hemorrhagic cerebrovascular insults were considered.